A comment on "Evaluating the reliability and seasonal sensitivity of a fitness-testing battery in elite youth soccer" - Lolli, L. (International Journal of Sports Physiology and Performance, 2026)
The recent study by Asimakidis et al1 assessed the reliability and seasonal sensitivity of proxy measures of lower-limb explosive strength, sprinting, change of direction, and endurance in 24 youth soccer players. Given the importance of knowing the amount of measurement error to inform practical judgments,2 small-scale reliability studies can be prone to a degree of uncertainty, preventing the understanding of whether any change in an applied observation can represent a real change in an athlete`s performance.2